Effect of oregano oil dietary supplementation on production parameters, height of intestinal villi and the antioxidant capacity in the breast of broiler - Fonseca-García, Ivette; Escalera-Valente, Francisco; Martínez-González, Sergio; Carmona-Gasca, Carlos A; Gutiérrez-Arenas, Diana A; Ávila-Ramos, Fidel (Austral Journal of Veterinary Sciences, 2017)
ABSTRACT. Oregano additives could contain growth stimulating compounds for poultry, however, a great variation attributed to their main components is observed. The aim of the present study was to investigate the effect of oregano oil dietary supplementation on the productive variables, the height of the intestinal villi and the accumulation of antioxidant compounds in the breast of broilers. In total, 480 broilers were reared from 1 to 42 d of age and since the first day of life were allocated into four treatments, each with four replications of 30 birds. The formulated diet was based on corn and soybean meal and 0, 100, 200 or 400 mg of oregano oil per kg of feed were incorporated in the diets of treatment 1, 2, 3 and 4, respectively. Feed intake, weight gain, feed conversion and mortality rates were weekly recorded. At 21 and 42 days of age the intestinal villi height and antioxidant capacity in the chicken breast were measured. Oregano oil used contained 43.17% and 29.16% of thymol and carvacrol, respectively. Feed intake, weight gain, feed conversion rate and mortality were not affected by oregano oil dietary supplementation. The height of intestinal villi increased with the level of oregano oil supplementation (P<0.05). However, the size of the intestinal villi was greater in the duodenum compared to the other parts (P<0.05), and jejunum and ileum had the same height. Antioxidant capacity of chicken breast at the 6th week was increased in the group that was dietary supplemented with 400 mg of oregano oil per kg of feed.